Alternatif Pemanfaatan Sampah Organik Sebagai Konservasi Sumber Energi Listrik - Sari, Fitria Novita (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2021)
The research article discussed the utilization of organic waste that always increases every year in line with the rate of population growth, therefore the article was prepared to review the utilization of organic waste as a form of conservation of electrical energy. The method in the research used is in the form of literature studies by collecting data from various sources or references relevant to the research conducted. The results of the literature study from several studies show that efforts to use organic waste derived from household waste, landfill waste, and organic waste in the market have the ability to be used for electrical energy sources and can be done energy conservation. The conclusion is that organic waste as an alternative to fossil fuels can be used as electrical energy, and that it can be used for energy conservation.